2020
DOI: 10.1097/mph.0000000000001816
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Imatinib Dosing With High-dose Methotrexate Leads to Acute Kidney Injury and Delayed Methotrexate Clearance in Pediatric Patients With Philadelphia Chromosome-positive B-Cell Acute Lymphoblastic Leukemia

Abstract: Imatinib, a tyrosine kinase inhibitor has improved survival in pediatric patients with Philadelphia chromosome-positive B-cell acute lymphoblastic leukemia. There are no formal drug interactions listed between methotrexate and tyrosine kinase inhibitors. Four pediatric patients with Philadelphia chromosome-positive B-cell acute lymphoblastic leukemia had delayed methotrexate clearance during their first cycle of high-dose methotrexate while receiving imatinib, resulting in acute kidney injury. For subsequent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It is unclear whether the association of the administration of diuretics and MTX CL is because of the nephrotoxicity caused by diuretics or due to MTX‐induced nephrotoxicity that triggers the clinical use of diuretics. The association between an increase in MTX CL and concomitant use of TKIs has also been described previously 58,59 and has caused some paediatric hospitals to hold TKIs from the start of HDMTX until it is cleared. This drug–drug interaction may be mediated by the SLCO1B1 transporter because both MTX and TKIs are substrates of the transporter and the TKIs may also regulate the transporter's function 60‐62 .…”
Section: Discussionmentioning
confidence: 63%
“…It is unclear whether the association of the administration of diuretics and MTX CL is because of the nephrotoxicity caused by diuretics or due to MTX‐induced nephrotoxicity that triggers the clinical use of diuretics. The association between an increase in MTX CL and concomitant use of TKIs has also been described previously 58,59 and has caused some paediatric hospitals to hold TKIs from the start of HDMTX until it is cleared. This drug–drug interaction may be mediated by the SLCO1B1 transporter because both MTX and TKIs are substrates of the transporter and the TKIs may also regulate the transporter's function 60‐62 .…”
Section: Discussionmentioning
confidence: 63%
“… 10 There have also been recent case reports of delayed MTX clearance caused by concomitant use of imatinib. 18 , 19 The TKI mechanisms affecting MTX metabolism need to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Our drug–drug interaction list did not include tyrosine kinase inhibitors like imatinib and dasatinib. However, it has been recently reported that such drugs may reduce MTX clearance and should therefore also be avoided during HD‐MTX treatment [20, 21].…”
Section: Discussionmentioning
confidence: 99%